Cu(I)‐Catalyzed Microwave‐Assisted Multicomponent Reaction Towards Synthesis of Diverse Fluorescent Quinazolino[4, 3‐b]quinazolin‐8‐ones and Their Photophysical Study. Issue 14 (11th April 2022) - Pawar, Gaurav; Ghouse, Shaikh Mohammad; Joshi, Swanand Vinayak; Rana, Preeti; Kar, Swayamsiddha; Sarma, P. Mahesh; Dannarm, Srinivas Reddy; Sonti, Rajesh; Nanduri, Srinivas
Abstract: A novel, base‐ and ligand‐free one pot protocol for the synthesis of fused‐quinazolinone under microwave irradiation using environmentally friendly PEG‐400 as a solvent has been developed. Besides benzaldehyde, various benzyl alcohols and methyl arenes were used in this protocol, which extend its synthetic applicability. Photophysical study of this highly fluorescent framework was studied by fluorescent study. DFT and ESI/MS studies were carried out to justify the proposed mechanism. Abstract : Microwave‐Assisted Copper‐catalyzed synthesis of quinozolino[4, 3‐ b ]quinazolin‐8‐ones via C−N bond formation using TMSN3  as an ammonia source. Density functional theory (DFT) calculations are performed for validating the proposed mechanistic rationale The synthesized compounds displayed high fluorescent properties. UV‐Vis, fluorescence, quantum yield, and Stokes shift calculations were used to analyze photophysical properties quantitatively.This developed protocol represents a novel development in copper catalysis in relation to sustainable C−N bond formation for the synthesis of fused quinazolinones.